A Flow Cytometric Assay of Platelet Activation Marker P-Selectin (CD62P) Distinguishes Heparin-induced Thrombocytopenia (HIT) from HIT with Thrombosis (HITT) - Jy, Wenche; Mao, Wei Wei; Horstman, Lawrence L.; Valant, Peter A.; Ahn, Yeon S. (Thrombosis and Haemostasis, 1999)
Heparin induced thrombocytopenia (HIT) is a well-known complication of heparin administration but usually resolves upon discontinuation without sequelae. However, a small proportion of HIT patients develop thrombosis associated with HIT, designated as HITT, which is often life-threatening and may lead to gangrene and amputations. Existing laboratory methods of confirming HIT/HITT do not distinguish between HIT and HITT. We report a flow cytometric assay of platelet activation marker CD62P to distinguish the effects of addition of HIT vs. HITT plasma to normal blood. Briefly, normal whole blood was incubated with platelet-poor plasma from 12 patients with HITT, 30 with HIT, and 65 controls, in presence and absence of heparin, and expression of CD62P was assayed by flow cytometry. When the ratios of fluorescent intensity of CD62P with heparin divided by that without heparin were compared, HITT plasma induced significantly higher ratios than HIT plasma (HITT ratios ~2.5 vs. HIT ratios ~1.2; p <0.001). Eleven of 12 HITT patients were positive by this test but only 5 of 30 HIT patients were positive (p < 0.0005). In a case of HIT with silent thrombosis, this assay gave a positive results prior to clinically evident thrombosis. In conclusion, this method distinguishes HITT from HIT and may be clinically useful in the detection of HITT, allowing early intervention for preventing catastrophic thrombosis.
Keywords: Heparin-induced thrombocytopenia; thrombosis; thrombocytopenia; drug-induced antibodies; heparin; platelet activation; P-selectin; CD62; CD36